2010
DOI: 10.1213/ane.0b013e3181c91ebc
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Effects of Vasopressors on the Fetoplacental Circulation of the Dual Perfused Human Placenta

Abstract: In the dual perfused, single isolated cotyledon, human placental model, exposure of the maternal circulation to ephedrine and phenylephrine caused an increase in FAP, whereas exposure to norepinephrine, epinephrine, and methoxamine did not. The pharmacodynamic mechanisms underlying these differences have yet to be explained. Thus, the clinical implications of the findings are as yet unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…However, norepinephrine restored the decreased peripheral vascular resistance less than phenylephrine [9]. In 2010, Minzter et al [36] reported that norepinephrine had no effect on fetal arterial perfusion pressure and fetoplacental microcirculation was not compromised. In the present study, no difference in fetal umbilical artery PO 2 was detected, suggesting that norepinephrine might not compromise fetal oxygen supply when compared with ephedrine in a bolus regimen.…”
Section: Discussionmentioning
confidence: 99%
“…However, norepinephrine restored the decreased peripheral vascular resistance less than phenylephrine [9]. In 2010, Minzter et al [36] reported that norepinephrine had no effect on fetal arterial perfusion pressure and fetoplacental microcirculation was not compromised. In the present study, no difference in fetal umbilical artery PO 2 was detected, suggesting that norepinephrine might not compromise fetal oxygen supply when compared with ephedrine in a bolus regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Minzter et al . [ 11 ] reported that norepinephrine had no effect on fetal arterial perfusion pressure, and the fetoplacental microcirculation was not compromised.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the effect of methoxamine on uteroplacental flow is also controversial. Wright et al demonstrated that methoxamine was associated with significant increase in uteroplacental resistance and flow [ 15 ], whereas Mintzer et al showed methoxamine had no effect on uterine blood flow and the fetal arterial perfusion pressure [ 27 ]. Because these side effects of methoxamine in obstetrics are potential and controversial, we think it is also safe for obstetric patients.…”
Section: Discussionmentioning
confidence: 99%